Validation Strategy for Pulmonary Vein Isolation in Patients With Paroxysmal Atrial Fibrillation in Long-Term Maintaining Sinus Rhythm: A Randomized Controlled Study - Xinyu Li; Houdeng Yu; Shihuang Lai; Yaqi Liao; Yihong Yang; Kejun Tian; Yiming Zhong; Xinguang Chen (Cardiology Research and Practice)
Conclusion: Rigorous validation can reveal dormant conduction in more than two-thirds of patients with PAF undergoing PVI. However, rigorous validation and additional ablation of the resulting connections do not improve long-term outcomes when a protocol that includes electrophysiological confirmation and pharmacological validation is used.